The Evolution of STEAM-Based Programs: Fostering Critical Thinking, Collaboration, and Real-World Application - Wised, Samran; Inthanon, Worawut (Journal of Education and Learning Reviews, 2024)
Background and Aims: STEAM education is critical because it combines technical and creative disciplines, fostering skills like critical thinking, problem-solving, and collaboration. This comprehensive approach prepares students to face complex, real-world challenges while also providing them with the adaptable skills required for the 21st-century workforce. This paper aims to investigate the Evolution of STEAM-Based Programs: Fostering Critical Thinking, Collaboration, and Real-World Application. Methodology: This paper employs a comprehensive methodology, including a systematic review of existing STEAM education research. It examines key trends, case studies, and educational frameworks to assess how STEAM programs have evolved and how they affect critical thinking, collaboration, and real-world applications. The article brings together findings from various sources to provide a comprehensive understanding of the effectiveness and challenges of STEAM-based approaches in education. Results: The study discovered that STEAM education combines science, technology, engineering, the arts, and mathematics to improve critical thinking, creativity, and problem-solving abilities. This approach not only improves student engagement and academic performance but also prepares students for future careers by teaching them 21st-century skills. STEAM education transforms students into innovative problem solvers who are prepared to face complex global challenges by cultivating a combination of technical and creative abilities. Conclusion: STEAM education combines science, technology, engineering, the arts, and mathematics to promote critical thinking, creativity, and problem-solving abilities. This integrated approach boosts student engagement and equips students with the adaptable skills required for future careers and global opportunities.